2021
DOI: 10.3390/su13105581
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Financial Inclusion on Sustainable Economic Growth in Sub-Saharan African Nations

Abstract: The primary concern of this examination is to systematically survey the importance of inclusive access to finance on the growth in terms of the economy in 48 sub-Saharan African (SSA) sovereign states with periodicity from 1995 to 2017. This study reports the results using both static and dynamic estimation techniques. For consistency, the baseline finding of the study estimation is based on the Generalized Method of Moments (GMM) system GMM. This article finds that there is a complimentary association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…[14] In Sub-Saharian Africa, scholars found that "there is a complimentary association (correlation) between the present degree of inclusiveness of finance and economic advancement in SSA." [3] Indian studies also identified similar results of "a positive association between economic growth and various dimensions of financial inclusion." [27] However, most works of literature are China-based studies and are categorized into three main themes: rural revitalization and sustainable economic growth in the form of a green economy and promoting small and micro enterprises (SMEs).…”
Section: Literature Reviewmentioning
confidence: 56%
“…[14] In Sub-Saharian Africa, scholars found that "there is a complimentary association (correlation) between the present degree of inclusiveness of finance and economic advancement in SSA." [3] Indian studies also identified similar results of "a positive association between economic growth and various dimensions of financial inclusion." [27] However, most works of literature are China-based studies and are categorized into three main themes: rural revitalization and sustainable economic growth in the form of a green economy and promoting small and micro enterprises (SMEs).…”
Section: Literature Reviewmentioning
confidence: 56%
“…The impact factor of sponge city speed on economic growth in lag three is also positive, with a coefficient of 0.2160; this is significant at a 5% confidence level, thus proving that sponge city construction also contributes significantly to economic growth, mainly because of the scale effect of urban industry and the modernization of agriculture in the countryside. Moreover, this contributes significantly to the economic development of the northern region [ 57 , 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Empirical Analysismentioning
confidence: 99%
“…Remarkably, strategic management of entrepreneurs is explicitly encapsulated in their capability to increase revenue-base and lessening of expenses (see Akinbode, Dipeolu, Bolarinwa & Olukowi, 2020;Chima et al, 2021;Alford & Greve, 2023). According to Peter Drucker in 1954, organizations see management by objective (MBO) as a philosophy and approach via which the strategic plans of entrepreneurs are realized.…”
Section: Introductionmentioning
confidence: 99%